Assume a solution of the form [tex]\Psi(x,y)=C[/tex]. Differentiating both sides gives
[tex]\Psi_x\,\mathrm dx+\Psi_y\,\mathrm dy=0[/tex]
with [tex]\Psi_x=y[/tex] and [tex]\Psi_y=x(\ln x-\ln y-1)[/tex].
Divide both sides by [tex]x[/tex] and we have
[tex]\dfrac yx\,\mathrm dx+(\ln x-\ln y-1)\,\mathrm dy=0[/tex]
Notice that
[tex]\left(\dfrac yx\right)_y=\dfrac1x[/tex]
[tex]\left(\ln x-\ln y-1\right)_x=\dfrac1x[/tex]
so the ODE is exact. Now we can look for a solution [tex]\Psi[/tex] with
[tex]\Psi_x=\dfrac yx[/tex]
[tex]\Psi_y=\ln x-\ln y-1[/tex]
Integrating the first PDE with respect to [tex]x[/tex] gives
[tex]\Psi(x,y)=y\ln x+f(y)[/tex]
and differentiating this with respect to [tex]y[/tex] gives
[tex]\Psi_y=\ln x+f'(y)=\ln x-\ln y-1\implies f'(y)=-\ln y-1\implies f(y)=-y\ln y+C[/tex]
So this ODE has general solution
[tex]y\ln x-y\ln y=C[/tex]
Given that [tex]y(1)=e[/tex], we have
[tex]e\ln1-e\ln e=C\implies C=-e[/tex]
so the particular solution is
[tex]y(\ln x-\ln y)=-e[/tex]
[tex]y\ln\dfrac xy=-e[/tex]
[tex]\boxed{y\ln\dfrac yx=e}[/tex]